World trade, 1800-1938: a new data-set - Giovanni Federico; Antonio Tena-Junguito (European Historical Economics Society (EHES), 2016)
This paper presents our data-base on world trade from 1800 to 1938. We have collected or estimated series of imports and exports, at current and constant (1913) prices and at current and at constant (1913) borders, for 149 polities. After a short review of the available series, we describe the methods for the construction of the data-base. We then deal with the criteria for the inclusion of polities, the representativeness of our series, the main types of sources, the procedures of deflation and, when necessary, of adjustments to 1913 borders. We discuss the details of the estimation of our polity series in Appendix B. Following Feinstein and Thomas (2001), we assess the reliability of our polity estimates. In the last two sections we present our trade series at current and 1913 borders and compare them with other available series. All data are available in a World Trade 1800-1938 Appendix Excel File
Keywords: F14; N10; 330; World Trade; new series; 19th and 20th century